THE IMPACT OF THE ACTIVITIES OF NON-RESIDENTS BANKS ON THE NATIONAL ECONOMY - Dauylbaev Kuandyk,; Kalieva Gulbakhyt,; Tasmaganbetov Tuktibay,; Zarina Esszhanova,; A. Masabaeva, (Academic Journal of Physical and Chemical Sciences, 2020)
The paper examines the effectiveness of the operations of non-resident banks in Kazakhstan. Performance assessment of non-resident banks in the local banking market is based on the model developed by the authors. The model is based on the indicators of the system of national accounts, and includes three stages of analysis: evaluation of the impact on real economy, estimation of performance of the intermediation function of a bank and the assessment of the bank’s stability. The object of study is Russian commercial banks operating in the Republic of Kazakhstan. In the study, the major factors contributing to the development of Russian banks in the financial market of the Republic of Kazakhstan are identified. In the present day circumstances all countries in the world experience the impact of the dynamic processes of globalization and integration. It differs from country to country: these processes have a considerable, often adverse, impact on developing countries, as indicated by some prominent economists, for example, J. Stiglitz [1]. Promotion of regional economic integration in its essence is considered only with regard to trade and partly investment cooperation. At the same time, undeservedly less attention is paid to the activities of commercial banks as to important financial intermediaries participating in the replenishment process. In these circumstances, it is important to analyze the issues associated with the improvement of performance efficiency of non-resident bank in the Kazakhstan banking sector. The aim of the paper is to investigate the impact of the activities of non-resident banks on the national economy and to develop an adequate methodology for their efficiency assessment. The choice of the object has been determined by the following preconditions: integration economic development of the two countries; the transition of both countries to the innovative model of development and restructuring of the national economy, development of the legal and institutional infrastructure for establishment of the common financial area between the two counties; functioning of the Customs Union since 1 January, 2010, the presence of favorable financial conditions for the participation of Russian banks in the banking market of Kazakhstan and other factors. The research methods used in this paper are: systematic approach, statistical, logical, and comparative analysis of the scientific literature, the analysis of bank annual reports. The analysis revealed that the Russian banks in Kazakhstan are actively encouraging the sphere of circulation, increasing inflation in the country. The Russian banks in Kazakhstan contribute to increase of redistribution of incomes, but do not develop the real sector and its innovation component in the Republic of Kazakhstan. The object of the research is Russian banking capital in the Kazakhstan market. The choice of the object has been determined by the following pre-conditions: Integrated economic development of the two countries that provides for mutual commercial, economic, and cultural relations; The transition of both countries to the innovative model of economic development and restructuring of the national economy; Growing congruence between two countries with regard to the level of socio-economic development, selected models and resources for economic development; Cooperation between the countries under discussion in the field of the planned synchronization of the WTO accession process; Development of the legal and institutional infrastructure for establishment of the common financial area between the two counties; Functioning of the Customs Union since 1 January, 2010, and other factors. Financial pre-conditions for the development of the favorable environment for participation of the Russian banks in the Kazakhstan market include: Uniformity of taxation systems of both countries, establishment of the national taxation systems on the basis of the Tax Code and their unification, identical elements in the taxation systems, coordinated reforms of the taxation systems; Considerable uniformity in the field of state finances: codification and harmonization of budgeting legislation on common principles; Current macroeconomic indicators pointing at the convergence of the economic development trends in the two countries: inflation rate, average weighted rate on long-term loans, public debt, etc. The level of development of the two countries is similar considering basic economic indicators; Provision of sufficient economic stability as a necessary premise for implementation of coordinated structural reforms of the economies of the two countries; Transition of the economies of both countries to the innovative development model and establishment of the common innovation space based on the usage of production, intellectual, technical and scientific potential of two states; Harmonization and unification of customs tariff policies aimed at support of new manufacturing enterprises and increase of investment potential of particular industries and agriculture.